2015
DOI: 10.1038/cr.2015.63
|View full text |Cite
|
Sign up to set email alerts
|

Park7 interacts with p47phox to direct NADPH oxidase-dependent ROS production and protect against sepsis

Abstract: Inappropriate inflammation responses contribute to mortality during sepsis. Through Toll-like receptors (TLRs), reactive oxygen species (ROS) produced by NADPH oxidase could modulate the inflammation responses. Parkinson disease (autosomal recessive, early onset) 7 (Park7) has a cytoprotective role by eliminating ROS. However, whether Park7 could modulate inflammation responses and mortality in sepsis is unclear. Here, we show that, compared with wild-type mice, Park7 −/− mice had significantly increased morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
57
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 53 publications
7
57
2
Order By: Relevance
“…Nox4 was constitutively active, the elevated Nox4 expression directly translated to increase ROS production [32]. Increasing evidences demonstrated that Nox4 played a detrimental role in process of inflammatory diseases, including sepsis [3,30,33]. Here, our results clearly showed that Nox4 was significantly increased in LPSinduced septic mice, which was accompanied by increased inflammatory mediators and inflammatory cytokines production.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Nox4 was constitutively active, the elevated Nox4 expression directly translated to increase ROS production [32]. Increasing evidences demonstrated that Nox4 played a detrimental role in process of inflammatory diseases, including sepsis [3,30,33]. Here, our results clearly showed that Nox4 was significantly increased in LPSinduced septic mice, which was accompanied by increased inflammatory mediators and inflammatory cytokines production.…”
Section: Discussionsupporting
confidence: 65%
“…Meanwhile, NADPH oxidase-dependent ROS played a detrimental role in lethal innate immune response in sepsis [4,30]. The role of oxidative stress in septic pathogenesis has been well appreciated [3,4]; however, the mechanisms by which oxidative stress contributed to pathogenesis were not well defined. There were at least seven isoforms of NADPH oxidase that have been identified, termed Nox1-Nox5, DUOX1, and DUOX2, and most of them were detected in immune cells, including macrophages [31].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a similar phenomenon was also seen in Park7 -/-mice and Stat2 -/-mice. In Park7 -/-mice, the increased mortality was mainly associated with aggravated lung injury and immunosuppression, along with the impaired bactericidal ability of macrophages (23). Here, we also found that swiprosin-1 deletion caused severe lung and kidney injury and immune paralysis, including impaired bacterial clearance and decreased HLA-DR in the macrophages.…”
Section: Discussionsupporting
confidence: 55%
“…Other PD-related genes have been reported to affect NOX activation. DJ-1/Park7 can bind to p47phox to alter NOX activation [222, 223], and silencing of DJ-1 has been shown to increase NOX4 expression and ROS production [224]. In addition, NOX has been implicated as a potential mechanism underlying neuronal vulnerability associated with PINK1 dysfunction [225].…”
Section: Introductionmentioning
confidence: 99%